(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The purpose of the article is to discuss some issues as well as some features of euphemisms in literal texts. The article illustrates some types of euphemisms as a literal and stylistic device. Moreover, some examples are given which euphemisms are used in literal texts.